A new monoterpene and a new sesquiterpene from the roots of Ageratina adenophora. (April 2018) - Luo, Bi; Dong, Li-Mei; Xu, Qiao-Lin; Zhang, Xu; Zhang, Qiang; Liu, Wen-Bin; Tan, Jian-Wen
Graphical abstract: Highlights: A new monoterpene (1 ) and a new sesquiterpene (2 ) were isolated from Ageratina adenophora . Compounds3 –6 were obtained from the roots of A. adenophora for the first time. The structures of compounds1 and2 were elucidated by spectroscopic means. Compounds1, 3 and4 showed inhibitory activity against Gram-positive bacterial strains. Abstract: A new thymol type monoterpene, 2α-methoxyl-3β-methyl-6-(acetyl- O -methyl)-2, 3-dihydrobenzofuran (1 ), and a new cadinane-type sesquiterpenoid, 1, 6-dihydroxy-1-isopropyl-4, 7-dimethyl-3, 4-dihydronaphthalen-2(1 H )-one (2 ), were isolated from the roots of Ageratina adenophora, along with four known compounds, eupatorenone (3 ), 3-hydroxymuurola-4, 7(11)-dien-8-one (4 ), 9-oxoageraphorone (5 ) and (4R, 5S)-4-Hydroxy-5-isopropyl-2-methyl-2-cyclohexehone (6 ). Their structures were determined by spectroscopic methods, including nuclear magnetic resonance (NMR) and mass spectrometry (MS) techniques. These compounds were all isolated from the roots of this plant for the first time. Compounds1, 3 and4 showed in vitro bacteriostatic activity against three test Gram-positive bacteria with MIC values ranging from 12.5 to 50 μg/mL. While, no obvious inhibitory activity was detected for the other compounds.